Does internal and external research and development affect innovation of small and medium-sized enterprises? Evidence from India and Pakistan - Naqeeb Ur Rehman (Asian Development Bank Institute (ADBI), 2016)
This study investigates the impact of internal and external research and development (R&D) on the innovation performance of small and medium-sized enterprises (SMEs) in India and Pakistan. Micro-level data was obtained for 3,492 Indian and 696 Pakistani SMEs from the World Bank's Enterprise Survey, and bivariate probit estimation techniques were used. The results show that internal and external R&D positively affects product and process innovations. However, this effect is stronger for Indian SMEs. The negative relationship between firm size and innovation output implies that SMEs in both countries face resource constraints. Further, Indian SMEs are dominant in terms of undertaking internal R&D and generating product and process innovations relative to those in Pakistan. The complementary relationship between internal and external R&D has been examined for both countries. The study is unique in comparing Indian and Pakistani SMEs innovation activities using micro-level data. The results suggest that business managers can utilize a balanced combination of internal and external R&D to accelerate innovation output and increase absorptive capacity. Specifically, public support for innovation, such as R&D grants, subsidies, and tax credits, could encourage SMEs to undertake more radical innovations.
Keywords: D22; L25; O31; O32; 330; India; Pakistan; SME; R&D; innovation; technology; firm; product innovation; process innovation; external R&D; internal R&D; absorptive capacity; innovative capacity; public support; incentives; output; bank loans; subsidies; tax credit